Socialno-demografska gibanja na zgornjem gorenjskem med letoma 1961 in 2002 - Ferreira, Andreja (Zbornik gozdarstva in lesarstva, 2005)
The paper examines social-demographic trends in the Upper Gorenjska region (communities of Bled, Bohinj, Jesenice and Kranjska Gora) and compares them with the Slovene average. The trends were studies for the period from the first census held in 1869 to the last census implemented in 2002. More detailed demographic analyses (age, employment and education structure, share of daily migrants amongst the employed, share of rural population) were made for the 1961-2002 period, whereas the population's natural, migratory and general trends were analysed for the period from 1995 to 2003.
Keywords: Gorenjska; prebivalstvo; Slovenia; Slovenija; Upper Carniola